Design and performance of a robotic arm for farm use - Roshanianfard, Ali; Noguchi, Noboru; Kamata, Tatsuki (International Journal of Agricultural and Biological Engineering, 2019)
Smart technology which is the backbone of high-efficiency production opens a new horizon in sustainable agriculture. Nowadays, harvesting the heavy-weight crops is considered an arduous job, specifically in Japan which has faced a serious labor shortage in agricultural fields. In this study, a development procedure and evaluation of a 4-degrees-of-freedom articulated robotic arm is presented, and it provides an appropriate infrastructure to develop a smart harvesting robotic system for heavy-weight crops such as pumpkin, watermelon, melon, and cabbage. This robotic arm designed as an actuating unit of a robot tractor for the agricultural outdoor environment. In this regard, different degree of freedom was evaluated under consideration of economic and technical indexes to find an optimized mechanism. The controlling algorithm of the system was developed by consideration of kinematic and dynamic aspects of the real-world condition. A special harvesting methodology was developed based on optimum harvesting conditions. A controlling unit was developed by using PLC system. Experimental performance, accuracy, payload per weight, and repeatability of the system were measured. The payload per weight, overall average accuracy, and overall average repeatability of the robot were 0.21, 1.85 mm, and ±0.51 mm, respectively. The results indicated that the developed system had a front access, harvesting length, and workspace volume of 2.024 m, 1.36 m, and 8.27 m3, respectively. One of the significant advantages of the proposed robotic arm is its capability to use in different industries with minimum modifications.Keywords: agricultural robot, robotic arm, harvesting, modeling, simulation, designDOI: 10.25165/j.ijabe.20191201.3721Citation: Roshanianfard A, Noguchi N, Kamata T. Design and performance of a robotic arm for farm use. Int J Agric & Biol Eng, 2019; 12(1): 146–158.